Investigation of a Boiler's Furnace Aerodynamics with a Vortex Solid Fuel Combustion Scheme on Physical and Mathematical Models - Prokhorov V.B.,; Chernov S.L.; Kirichkov V.S.; Kaverin A.A. (Problems of the Regional Energetics, 2018)
The important problem of developing the low-cost technologies that will be able to provide a deep decrease in the concentration of nitrogen oxides while maintaining fuel burn-up efficiency is considered. This paper presents the results of the aerodynamics study of the furnace of boiler TPP-210A on the base of the physical and mathematical models in the case when boiler retrofitting from liquid to solid slag removal with two to three times reduction of nitrogen oxide emissions and replacing the vortex burners with direct-flow burners. The need for these studies is due to the fact that the direct-flow burners are "collective action" burners, and efficient fuel combustion can be provided only by the interaction of fuel jets, secondary and tertiary air jets in the furnace volume. The new scheme of air staged combustion in a system of vertical vortexes of opposite rotation with direct-flow burners and nozzles and direct injection of Kuznetsky lean coal dust was developed. In order to test the functional ability and efficiency of the proposed combustion scheme, studies on the physical model of the boiler furnace and the mathematical model of the experimental furnace bench for the case of an isothermal fluid flow were carried out. Comparison showed an acceptable degree of coincidence of these results. In all studied regimes, pronounced vortices remain in both the vertical and horizontal planes, that indicates a high degree of mass exchange between jets and combustion products and the furnace aerodynamics stability to changes in regime factors.